Institutional capacity for water conservation: a case study of Sedibeng District Municipality - Likontsane, Surprise C. (My University, 2016)
Since the democratic transition in 1994, the role of local government has changed dramatically. Local governments are now expected to play a far more active role in their constituencies. As such, municipalities are expected to implement broader national policies and legislatures. The literature reviewed as part of the research indicated that most municipalities are faced with inadequate performance skills to manage and sustain their projects. This particular study seeks to understand the institutional and human resources strengths and weaknesses that help or hinder Sedibeng municipality to actively pursue water conservation through implementing Integrated Water Resources Management (IWRM) principles. In pursuit of this purpose, a qualitative research approach was adopted with interviews conducted with Sedibeng Municipality’s seven senior officials and community members. The main findings of this study revealed that the key technical department of the water sector in Sedibeng has capacity challenges at individual and organizational level. Of special concern is the failure of the municipality to give ongoing training to staff, so as to pass on modern advanced knowledge and new technological innovation skills. This is further compounded by the mismatch between the qualifications and job descriptions of some staff members. The study also finds that public-private partnership between the municipalities and private companies is needed in the water sector to promote water conservation and thus provide a better level of service delivery. The research concludes that institutional capacity is a prerequisite for the implementation of IWRM principles. In regard to this study, it has been established that to some extent Sedibeng District Municipality has the required institutional capacity in terms of organizational arrangement to harness the principles of IWRM. The accomplishment of IWRM depends profoundly on financial and human capacity of each municipality. Therefore, the key recommendation is that the municipalities should employ individuals based on merit and work experience to ensure efficient management of funds and effective execution of water related projects. Key words: Water Conservation, IWRM, Institutional capacity, Sedibeng, Emfuleni
A research report submitted to the Faculty of the Built Environment and Engineering, University of the Witwatersrand, in partial fulfillment of the requirement for the degree of Master of Science in the field of Development Planning (MSc DP) August 2015
Keywords: Water resources development--South Africa; Water conservation--Africa, Southern; Water conservation--Economic aspects--South Africa; Water supply--South Africa